Investigating the relationship between pre‐service physics teachers' professional knowledge, self‐concept, and interest. Issue 7 (10th February 2019) - Sorge, Stefan; Keller, Melanie M.; Neumann, Knut; Möller, Jens
Abstract: This study investigates the relationships between professional knowledge, self‐concept, and interest of pre‐service physics teachers. In order to support student learning and interest development alike, teachers need a profound professional knowledge and respective motivational orientations. Developing both professional knowledge and motivational orientations in teachers is therefore a key challenge of teacher education. Prior research has focused on the development of content knowledge (CK) and pedagogical content knowledge (PCK) within teacher education, but the role of motivational orientations such as self‐concept and interest have mostly been neglected areas of study. As individuals develop domain‐specific motivational orientations, they compare their achievement in an external frame to the achievement of their peers, and they compare their achievements in an internal frame across domains. The effects of these psychological processes on domain‐specific motivational orientations are described by the generalized internal/external frame of reference model (GI/E model). We assessed the professional knowledge (CK and PCK) and motivational orientations (self‐concept and interest) of N = 200 pre‐service physics teachers from 12 teacher education institutes in Germany. To investigate the predictions of the GI/E model, we utilized structural equation modeling. In line with the GI/E model, the analysis revealed that pre‐service teachers use social comparisons. Pre‐service teachers with a higher CK/PCK also showed a higher CK/PCK self‐concept. We also identified instances of internal comparisons as we found that a high level of CK corresponds with a lower PCK self‐concept. While we could not identify the same effects from professional knowledge on interest, self‐concept mediated the effects from professional knowledge on interest. The results suggest that interdependencies between professional knowledge and motivational orientation should be given more consideration in teacher education research and should also be addressed more explicitly in teacher education.